Effect of Adding Lemongrass (Cymbopogon citratus) on Organoleptic Test, Cooking Loss, and pH of Salted Eggs - Dwijayanti, Rts. Sherly; Seda, Seilia Pebrioni; Imanuel, Robertho (Faculty of Animal Science Universitas Brawijaya, 2025)
Eggs are foodstuffs of animal origin that are a source of protein, the perishable nature of eggs causes the need for handling methods, one method of preserving eggs that has been done since long ago is by salting, the shortcomings of existing salted egg products are the absence of characteristics other than salty taste, one of the efforts to improve the quality of salted eggs can be done with the innovation of adding flavor from additives in the making. This study aims to determine the effect of the addition of lemongrass (Cymbopogon citratus) at a certain level on the taste and quality of salted eggs. This study used a completely randomized design (CRD) with four treatments and four replicates namely P0 (salted duck eggs without the addition of lemongrass), P1 (salted duck eggs with 5% lemongrass), P2 (salted duck eggs with 10% lemongrass), P3 (salted duck eggs with 15% lemongrass). The results of this study indicate that the addition of lemongrass to salted egg production at 15% was quite favorable among panelists in organoleptic tests, with an average preference score of 4.06 in the color and aroma tests, 4.13 in the taste test, and 4.0 in the texture test. However, in physical quality tests, cooking loss, and the pH of the salted eggs did not change after the addition of lemongrass (not significantly different).